LITERASI KEUANGAN DALAM PERSPEKTIF MAHASISWA: (STUDI KASUS MAHASISWA FEBI IAIN LHOKSEUMAWE) - ISMAULINA ISMAULINA; SURYANI SURYANI (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2019)
Every individual wants a happy and prosperous life. To achieve that it takes knowledge of ﬁnancial literacy in order for someone to avoid ﬁnancial problems. This study aims to examine how the level of ﬁnancialliteracy students majoring in Islamic economics Faculty of Economics and Business Islam (FEBI) IAINLhokseumawe. And whether the level of income aﬀects the management and ﬁnancial decisions of studentsof the Department of Sharia Economics FEBI IAIN Lhokseumawe. Respondents studied are students whocome from FEBI majoring in Sharia Economics amounted to 100 people. Mean and frequency test were usedin this study. The result of the study shows that the average score of ﬁnancial literacy students of EconomicsDepartment of FEBI IAIN Lhokseumawe of 3.27 (65.4%) means that the level of student ﬁnancial literacyis still far from the optimum or still quite enough, even close to the low category so it should be increasedespecially related to the knowledge of expenditure, credit, savings and investment. The average student incomelevel lies in the medium/moderate category of 56%. Giving meaning diﬀerences in student income levelsaﬀect ﬁnancial management and make the right ﬁnancial decisions.